1996
DOI: 10.1128/jb.178.10.2941-2947.1996
|View full text |Cite
|
Sign up to set email alerts
|

maoB, a gene that encodes a positive regulator of the monoamine oxidase gene (maoA) in Escherichia coli

Abstract: The structural gene for copper-and topa quinone-containing monoamine oxidase (maoA) and an unknown amine oxidase gene have been located at 30.9 min on the Escherichia coli chromosome. Deletion analysis showed that the unknown gene was located within a 1.1-kb cloned fragment adjacent to the maoA gene. The nucleotide sequence of this fragment was determined, and a single open reading frame (maoB) consisting of 903 bp was found. The gene encoded a polypeptide with a predicted molecular mass of 34,619 Da which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
2
29
1
Order By: Relevance
“…Thus, the catabolite repression of the Pmao A promoter, rather than being a direct effect on such promoter, may reflect the catabolite repression of the maoB gene (342). By using crp cya E. coli mutant strains that contained the maoB::lacZ fusion, it was shown that the catabolite repression by glucose was mediated by the cyclic AMP (cAMP)-CRP complex on the Pmao B promoter (Fig.…”
Section: Transcriptional Activatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the catabolite repression of the Pmao A promoter, rather than being a direct effect on such promoter, may reflect the catabolite repression of the maoB gene (342). By using crp cya E. coli mutant strains that contained the maoB::lacZ fusion, it was shown that the catabolite repression by glucose was mediated by the cyclic AMP (cAMP)-CRP complex on the Pmao B promoter (Fig.…”
Section: Transcriptional Activatorsmentioning
confidence: 99%
“…Amino acid sequence comparisons reveal that MaoB is also a member of the AraC family of regulators, having 22% sequence identity to the other AraC family member involved in catabolism of aromatics in E. coli, i.e., the HpaA protein (see above). The significant similarity between the C-terminal domain of MaoB and that of other members of the AraC family suggests that this domain binds to specific DNA in the maoA and padA promoters (Pmao A and Ppad), with the nonhomologous N-terminal and central region of MaoB being involved in the recognition of the inducer molecules, that is, tyramine and PEA (127,342) (Fig. 6A).…”
Section: Transcriptional Activatorsmentioning
confidence: 99%
“…As observed for the MhpR regulator, CRP also regulates expression of other transcription factors in E. coli such as MelR (Webster et al, 1988), MalT (Chapon & Kolb, 1983), RhaS (Wickstrum et al, 2005), MaoB (Yamashita et al, 1996), HcaR (Turlin et al, 2001), GalS (Weickert & Adhya, 1993), RpoH (Kallipolitis & Valentin-Hansen, 1998), BlgG (Gulati & Mahadevan, 2000), PrpR (Lee et al, 2005) and Fis (Nasser et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…CRP Mediates a Superimposed Level of Regulation on the Pa Promoter-It is known that some aromatic catabolic pathways in E. coli, such as the paa, hca, hpa, and mao-encoded pathways responsible for the catabolism of phenylacetate, phenylpropionate, 4-hydroxyphenylacetate, and 2-phenylethylamine, respectively, are repressed by the presence of glucose in the culture medium (26,27,(42)(43)(44)(45). To check whether the mhp cluster is also under catabolite repression control, E. coli AFM-CRAL cells were grown in glycerol-or glucose-containing minimal medium in the presence of 3HPP.…”
Section: In Vivo Characterization Of the Pa And Pr Promoters Andmentioning
confidence: 99%